FIR digital filter-based ZCDPLL for carrier recovery. Issue 4 (2nd April 2016) - Nasir, Qassim
Abstract : The objective of this work is to analyse the performance of the newly proposed two-tap FIR digital filter-based first-order zero-crossing digital phase-locked loop (ZCDPLL) in the absence or presence of additive white Gaussian noise (AWGN). The introduction of the two-tap FIR digital filter widens the lock range of a ZCDPLL and improves the loop's operation in the presence of AWGN. The FIR digital filter tap coefficients affect the loop convergence behaviour and appropriate selection of those gains should be taken into consideration. The new proposed loop has wider locking range and faster acquisition time and reduces the phase error variations in the presence of noise.